Etika Pemberian Pakan: Integrasi Prinsip Animal Welfare dan Hukum Islam dalam Pemenuhan Hak Ternak - Lestariningsih Lestariningsih; Arum Ayu Lestari (Universitas Nahdlatul Ulama Blitar, 2025)
This research is motivated by the urgency of the ethics of feeding in the livestock industry which often ignores the aspect of animal welfare for the sake of production efficiency, as well as the need to integrate the principle of halalan thayyiban in Islamic law to guarantee the basic rights of livestock. The purpose of this study is to map global literature trends regarding the interconnection between animal welfare and Islamic law and identify research gaps related to feed ethics. The method used is a systematic literature review study with bibliometric analysis through the VOSviewer software on publication metadata for the 2020–2026 period. The results show a significant surge in publications in the last five years, with the identification of four main clusters linking research ethics, veterinary compliance, the production industry sector, and the human education dimension. Overlay and density analysis revealed that the focus of research has shifted from basic moral theory to practical application at the industrial level, but there is still a gap in specific studies on the integration of Islamic law in the standardization of feed materials. The conclusion of the study confirms that the fulfillment of livestock rights is a multidisciplinary responsibility where Islamic law functions as a moral reinforcement of existing industrial compliance standards. It is recommended for future researchers to explore the comparative study of classical fiqh literature with modern feed technology, while livestock practitioners are expected to begin integrating animal welfare parameters into the halal assurance system to realize more ethical and religious livestock practices.